The Effect Of Some Speed Exercises On The Basic Skills Of Basketball Players - Boudjatate Ahmed; Cherifi Mohamed Amine; Bourenane Cherif Mustapha (University Of Eloued جامعة الوادي, 2024)
As the researcher was a basketball player, the aim of the research was to identify the degree of impact of certain speed exercises on basic techniques and their relation with the success of the basketball players. The researcher selected his research sample among second-class Kouba Star Olympic Club players for the year 2021-2022, whose number was (22). We obtained a correlation between the results of the research and the presence of a significant correlation between the rapid application of the planned exercises on the evolution of the level of certain types of speed, and the rapid application of the planned exercises on the evolution of the level of some basic basketball techniques. The researcher has, thus, recommended continuous work by applying the schematic exercises at a gradual speed until we reach their application at its maximum speed.
Keywords: speed exercises; Technical exercise; Basket Ball; players